Development of automatic healthcare instruction system via movement gesture sensor for paralysis patient - S. A. C. Aziz; A. F. Kadmin; N. Rahim; W. H. W. Hassan; I. F. A. Aziz; M. S. Hamid; R. A. Hamzah (Institute of Advanced Engineering and Science, 2019)
This paper presented an automatic healthcare system where the system able to help and facilitates the paralysis patient to complete their daily life. When a patient suffers from a paralysis attack, the whole or partial of their body maybe disabled to move which means their movement is restricted and they also barely to communicate with anyone because they are unable to speak like a normal person. It will be hard for medical staff to understand what they want to convey and in helping them to manage their daily needs such as eating, drinking, bathing and etc. By developing this project, the health officer can assist the paralyzed patient when they are alerted by the message from patient via GSM network. There are several instruction of movement gesture sensor presented in this paper in order to assist health officer in helping the paralyzed patient to complete their needs. Whenever the patient gives the simple hand movement instruction, then it will be delivered through SMS and the alerted notice will be display on notification board to alert the health officers for assisting the patient.